Molecular epidemiology of hepatitis B virus mutants associated with vaccine-escape, drug-resistance and diagnosis failure - Di Lello, Federico Alejandro (2019)
The massive implementation of the vaccine and antiviral agents against hepatitis B virus (HBV), targeting the envelope and viral polymerase genes, induces a selection pressure that might lead to the emergence of variants that impair the effectiveness of the vaccine, diagnostic methods and antiviral therapy. The aim of this study was to evaluate the prevalence of HBV vaccine escape mutants (VEMs), diagnostic failure mutants (DFMs) and treatment resistance mutants (ARMs) among individuals from Buenos Aires, Argentina. HBV surface antigen and polymerase sequences obtained from serum samples of 530 HBV-infected individuals were analysed. Samples belonged to genotypes A (28.1%), D (13.6%) and F (58.3%). VEMs, DMFs and ARMs were present in 40 (7.5%), 57 (10.7%) and 27 (5.1%) samples within the studied population. Additionally, eight nonpreviously reported VEMs and nine DFMs were identified. VEMs and DFMs were biased by genotype, being higher in genotype D (33.3% and 33.3%) compared to genotype A (6% and 17.4%) and genotype F (2.3% and 2.3%) (P > 0.001). On the contrary, there was no association between the presence of ARMs and HBV genotype (P = 0.324). VEMs, DFMs and ARMs create public health concerns. The current study provided valuable information about mutants in surface antigen and polymerase in HBV-infected patients from Argentina where HBV-F is the most prevalent genotype. Consequently, it constitutes an important reference for Latin American clinicians in order to optimize the management of HBV-infected patients.